The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2174/1874325001307010338
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Shoulder Instability and its Management

Abstract: The assessment and management of patients with instability of the shoulder joint can be challenging, due to the varying ways patients present, the array of different classification systems, the confusing terminology used and the differing potential management strategies. This review article aims to provide a clear explanation of the common concepts in shoulder instability and how they relate to the assessment and management of patients.There are sections covering the mechanisms of shoulder stability, the clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 47 publications
0
32
0
2
Order By: Relevance
“…Waldt et al found that 86% of patients with acute anterior instability had arthroscopically proven Bankart lesions (46). Evidence supports arthroscopic surgical intervention for Bankart lesions in patients with traumatic, unidirectional instability and Bankart lesion often requiring surgery, as there is a substantial reduction in rate of recurrence with stabiliza-tion (47). CT assessment of bone stock should be considered when the Bankart fragment involves more than 25% of the glenoid face, given the likelihood of open repair and surgical bone grafting in this cohort (48).…”
Section: Classic Bankart Lesionsmentioning
confidence: 99%
“…Waldt et al found that 86% of patients with acute anterior instability had arthroscopically proven Bankart lesions (46). Evidence supports arthroscopic surgical intervention for Bankart lesions in patients with traumatic, unidirectional instability and Bankart lesion often requiring surgery, as there is a substantial reduction in rate of recurrence with stabiliza-tion (47). CT assessment of bone stock should be considered when the Bankart fragment involves more than 25% of the glenoid face, given the likelihood of open repair and surgical bone grafting in this cohort (48).…”
Section: Classic Bankart Lesionsmentioning
confidence: 99%
“…7,24 Unlike glenohumeral dislocation, which requires a manual reduction, the diagnosis of traumatic anterior glenohumeral subluxation is often more elusive and cannot be objectively documented and quantified with similar accuracy. 27 …”
Section: Diagnosismentioning
confidence: 99%
“…7 These classification systems take into account the etiology, direction, and type of instability. 37 The type of instability ranges from subluxation to dislocation.…”
Section: Classificationmentioning
confidence: 99%
“…In the abducted position (90°), the anteroinferior glenohumeral ligament (AIGHL) provides the main source of resistance to anterior dislocation, while the middle and superior glenohumeral ligaments provide resistance in the mid-abducted (45°) and adducted positions, respectively. The most common mechanism for anteroinferior dislocation is a traumatic event that places the shoulder in extremes of abduction and external rotation [5]. These exaggerated maneuvers result in injuries to the corresponding soft tissues (anteroinferior capsule-labral complex or Bankart lesion) or bony structures (anteroinferior glenoid or posterosuperior humeral head).…”
Section: Introductionmentioning
confidence: 99%